Correction of Murine Diabetic Hyperglycaemia With A Single Systemic Administration of An AAV2/8 Vector Containing A Novel Codon Optimized Human Insulin Gene - Uin, Gan Shu (BENTHAM SCIENCE PUBL LTD, 2021)
CURRENT GENE THERAPY